Reforma Curricular Da Rede Municipal De Ensino De São Paulo (2013): Concepções De Alfabetização E Letramento Em Duas Escolas Localizadas Em Territórios Vulneráveis - Santos, Vanessa Santana Dos [UNIFESP] (2017)
The present work had as object of study the implementation of the guidelines of the document Program of Curricular and Administrative Reorganization, Expansion and Strengthening of the Municipal Education System of São Paulo (2013), which restructured the Cycles of Elementary Education in: Alphabetization Cycle – 1 st to 3rd year, Interdisciplinary Cycle - 4th to 6th year, and Authorial Cycle - 7th to 9th year, delimited in the Alphabetization Cycle that proposes that all children to be literate until the age of eight, at the end of the 3rd year of the Alphabetization Cycle (BRAZIL, 2012a). It is understood that the discussion about literacy was more emphatic from the Republic and, over time, the term has undergone changes in its meaning, with implications in the pedagogical practice. In the 1980s, the “literacy” neologism emerged (TFOUNI, 2010) that establishes the relationship between the use of writing and social practices. Considering the changes in the new curricular proposal of the city of São Paulo and the conceptions of literacy and literacy that emerged throughout the reforms, the following problematization is proposed: Which conceptions of alphabetization and literacy are present in the municipal curriculum of the city of São Paulo and the pedagogical practices of the teachers of two schools located in vulnerable territories? For this, the main objective of the research was to comprehend the conceptions of alphabetizing and literacy in the Program of Curricular and Administrative Reorganization, Expansion and Strengthening of the Municipal Education System of São Paulo – More Education São Paulo and their relations to pedagogical practices of the teachers who teach in the two schools located in vulnerable territories. In this sense, the intention was, from a historical perspective, to raise the conceptions of alphabetization in the four moments of its history (MORTATTI, 2000, 2006), as well the insertion of literacy in the end of 19th century. In addition, to identify the influence of international organizations in relation to alphabetization in Brazilian public policies, as well as the influence of certain concepts of alphabetization and literacy derived from the academic field in official documents, among them: National Curriculum Parameters of Portuguese Language (PCNLP), The Program for the training of alphabetizing teachers (PROFA) and the Pro-Literacy and, specifically, at the municipal level; to analyze the curricular and administrative reform of the Municipal Department of Education (SME/SP) and the concepts of alphabetization and literacy contained in it, based on the Curricular Guidelines and proposition of learning expectations for Elementary School-Cycle I, document previous to the reform, and the Conceptual and Methodological Elements to define the Learning Rights and development of the Literacy Cycle (1st, 2nd and 3rd years) of Elementary School and PNAIC, considered, by the official document, as principles of the reorganization of the Municipal Teaching Network of São Paulo; finally, to understand the pedagogical practices of the teachers who teach in vulnerable territories, starting from the official documents already analyzed, from the perspective of alphabetizing through teaching to read and to write. This was a qualitative research that used the Policy Cycle (Ball, 1994) and its contexts: influence, production and practice. In the context of influence, we sought the origin of literacy and literacy and the actions of international organizations in Brazilian documents. In the production, we tried to raise the conceptions of literacy and literacy in official documents. Finally, in the context of practice, through semi-structured interviews, analysis of schoolbooks and observations in loco, we aimed to articulate these research instruments to understand pedagogical practices. It was concluded that the political texts underwent re-creations and recontextualization according to the conceptions and perspectives of the teachers who reformulated the policies of the alphabetizing through teaching to read and write section, in a different way from what was presented.